Internal Ties and Stock Price Crash Risk: Evidence from Chinese Listed Firms. - Zhou, Jian; Yu, Jianglong; Lei, Xiaodong (Abacus, 2025)
Drawing on information advantage and executive entrenchment perspectives, this study examines the impact of internal ties between independent directors and non‐CEO executives (hereafter, internal ties) on stock price crashes. Utilizing a dataset covering Chinese listed firms spanning 2005 to 2021, we find that internal ties alleviate information asymmetry between the board and management, reducing future stock price crash risk. This supports the information advantage hypothesis. Further analysis reveals the effect of internal ties on stock price crash risk is more evident in high social trust regions and among non‐state‐owned enterprises (non‐SOEs). Mechanism tests demonstrate that financial opacity and financial reporting conservatism are economic mechanisms through which internal ties affect stock price crashes. Our research sheds new light regarding the significance of internal ties in corporate governance and enriches the literature on internal governance.